SISTEMATISASI PERIZINAN LAPAK DENGAN MODEL WATERFALL UNTUK PENDAFTARAN IZIN USAHA - Lia Syaputri; Endrika Syahrani; Muhammad Rivan; Janu Suhanda; Sri Rahayu (Jurnal Riset Teknik Komputer, 2024)
This article presents the development of a digital-based business permit system using the Waterfall model, which aims to simplify and speed up the process of systematically registering business permits. Through the Waterfall model, development is carried out in sequential stages, starting from needs analysis to system implementation and maintenance. The resulting system is expected to replace slow and often inefficient manual processes, by providing a solution that is more structured, transparent and easily accessible to users. The research results show that implementing the Waterfall model is able to increase time efficiency and accuracy of the licensing process, while providing a better user experience. This digital licensing system is expected to support the growth of small and medium businesses, simplify the business legalization process, and contribute to increasing business actors' compliance with government regulations.